Study on the cocrystal formation of ibuprofen and oxalic acid via evaporation method: article / Nor Adila A. Rahman - A. Rahman, Nor Adila; Othman, Muhamad Fitri
Co-crystallization is the process where the combination of two compound which are active pharmaceutical ingredient (API) compound with the co-former by the noncovalent interaction. This process is believed that it can enhanced the physicochemical properties of the API including solubility, stability, dissolution rate, melting point and its bioavailability. Due to this, the research for the co-crystallization of the Ibuprofen and oxalic acid had conducted as it co-former by using the slow evaporation method. The analyzation and characterization of this co-crystal had conducted by using the optical microscope, Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimeter (DSC) and X-ray diffraction (XRD). The observation using optical microscope had shown that the cocrystal grew in the dendrite and rod shape. From the characterization of the cocrystals in FTIR, it shows the shift of peak which can be shown the cocrystal structure had performed. Then, the DSC showed that the melting point of cocrystals were higher than the pure ibuprofen. This showed that the cocrystal had higher thermodynamic stability than the pure its API. The characterization of the IBP:OA cocrystal by using the XRD had proved that there are new crystallographic structure formed by comparing it with the pure compound. These results showed the cocrystals had formed.